Signaler and receiver boldness influence response to alarm calls in eastern chipmunks. (30th November 2017) - Couchoux, Charline; Clermont, Jeanne; Garant, Dany; Réale, Denis
Abstract : Personality affects response to alarm calls. This study reveals that boldness explains how vigilant chipmunks behave in response to alarm calls, and that vigilance diminishes in response to shyer callers. Chipmunks thus evaluate the personality of callers and discount the danger associated with calls from highly risk-sensitive individuals. Adjusting responsiveness relative to caller reliability improves foraging while reducing the risk of predation. Abstract: Using social information can benefit individuals in many ways. Responding to alarm signals can, for instance, maximize survival under predation risk. However, foraging individuals should consider the reliability of such risk-based information to balance antipredator behavior and resource acquisition. Receiver decisions could depend on personality effects, as individual variation in risk-taking tendencies (i.e., boldness) could not only affect receiver perception of the signaled threat but also signaler reliability. Recent theoretical models support the possibility of coevolution between personality and communication strategies. Using a playback experiment, we show that wild eastern chipmunks ( Tamias striatus ) respond to alarm calls according to their own boldness level (measured as consistent individual differences in basal vigilance) and that they increase their vigilance response to bolder callers potentially considered as more reliable. Further, receivers respond to the callers' boldness regardless of their own boldness and independently of their familiarity level with callers, therefore decoding this information from vocalizations. Such effects of individual behavioral variation on the perception and interpretation of social information could apply to signals used in a variety of ecological contexts.